Efek Samping Kemoterapi Mempengaruhi Tingkat Kepatuhan Pengobatan Anak Leukemia Limfoblastik Akut - Dandi Putra Nurfajriansyah; Ieva Baniasih Akbar; Widayanti (Bandung Conference Series: Medical Science, 2023)
Abstract. The primary treatment for ALL is chemotherapy. The side effects of chemotherapy drugs that appear will depend on the chemotherapy drugs given to the patient. Non-adherence plays a role in the failure of chemotherapy. This study aims to analyse the relationship between the side effects of chemotherapy drugs and the level of adherence to treatment of pediatric acute lymphoblastic leukemia patients at Al-Islam Hospital Bandung. This research method is an observational analytic approach to cross-sectional. The sample of this research is 50 people with total sampling technique in ALL pediatric patients at Al-Islam Hospital Bandung. Data was collected using a questionnaire called Pediatric-Patient Reported Outcome-Common Terminology Criteria for Adverse Events (Ped-PRO-CTCAE) and Medication Adherence Rating Scale (MARS). Data analysis using chi-squares test. This study showed that subjects who experienced side effects were in the criteria grade 1 such nausea, vomiting, alopecia, dry mouth, and fatigue are 74%, and high percentage of adherence rate of are 78%. Test results obtained a value of p = 0.015 (p <0.05), which shows a relationship between the side effects of chemotherapy drugs and the level of adherence to treatment of pediatric acute lymphoblastic leukemia patients at Al-Islam Hospital Bandung. Level of adherence to treatment effect the success of chemotherapy. Abstrak. Pengobatan ALL utamanya dengan kemoterapi. Efek samping obat kemoterapi yang muncul akan bergantung pada obat kemoterapi yang diberikan kepada pasien. Ketidakpatuhan berperan dalam kegagalan kemoterapi. Penelitian ini bertujuan untuk menganalisis hubungan efek samping obat kemoterapi dengan tingkat kepatuhan pengobatan pasien anak leukemia limfoblastik akut di RS Al-Islam Bandung. Metode penelitian ini adalah analitik observasional dengan pendekatan potong lintang. Sampel penelitian ini adalah 50 orang dengan teknik total sampling pada pasien anak ALL di RS Al-Islam Bandung. Pengumpulan data dilakukan menggunakan kuesioner Pediatric-Patient Reported Outcome-Common Terminology Criteria for Adverse Events (Ped-PRO-CTCAE) dan Medication Adherence Rating Scale (MARS). Analisis data menggunakan uji chi–square. Hasil penelitian ini menunjukkan subjek yang mengalami efek samping dalam kriteria grade 1 seperti mual muntah, alopesia, dan mulut kering sebanyak 74% dan persentase tingkat kepatuhan tinggi sebanyak 78%. Hasil uji didapatkan nilai p=0,015 (p<0,05) yang menunjukkan terdapat hubungan antara efek samping obat kemoterapi dengan tingkat kepatuhan pengobatan pasien anak leukemia limfoblastik akut di RS Al-Islam Bandung. Kepatuhan pengobatan kemoterapi dapat mempengaruhi keberhasilan kemoterapi.